Liquid Metal-Embedded Layered-PDMS Antenna for Flexible and Conformal Applications - Wang, Meng; Liu, Zhifu; Dong, Jian (Frontiers in Physics, 2022)
This paper proposes a dual-band slot IFA antenna using a combined technique of liquid metal (LM) filling and polydimethylsiloxane (PDMS) substrate. The antenna working at 2.4 GHz and 5.8 GHz consists of three LM layers- radiation patch, short circuit stub and ground plane and can be bent to different radiuses for flexible, conformal and wearable applications. The vacuum filling method enables realization of a monolithic integrated substrate. The applicability of this antenna for wearable wristband is validated through simulation.